2004
DOI: 10.1016/s0014-5793(04)00224-8
|View full text |Cite
|
Sign up to set email alerts
|

Lignin dehydrogenative polymerization mechanism: a poplar cell wall peroxidase directly oxidizes polymer lignin and produces in vitro dehydrogenative polymer rich in β‐O‐4 linkage

Abstract: An investigation was performed to determine whether lignin dehydrogenative polymerization proceeds via radical mediation or direct oxidation by peroxidases. It was found that coniferyl alcohol radical transferred quickly to sinapyl alcohol. The transfer to syringaresinol was slower, however, the transfer to polymeric lignols occurred very slightly. This result suggests that the radical mediator theory does not su⁄ciently explain the mechanism for dehydrogenative polymerization of lignin. A cationic cell wall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 20 publications
1
92
0
Order By: Relevance
“…In the case of basic peroxidases, the capacity of these enzymes to oxidize S moieties is universally accepted (Bernards et al, 1999;Quiroga et al, 2000;Ros Barceló and Pomar, 2001;Holm et al, 2003;Sasaki et al, 2004), and this observation would explain why antisense suppression of basic peroxidases in transgenic plants produces decreased levels of both G and S lignins (Blee et al, 2003), while antisense suppression of acidic peroxidases produces only decreased levels of G lignins (Li et al, 2003).…”
Section: Discussion Basic Zeprxs In Sccmentioning
confidence: 99%
“…In the case of basic peroxidases, the capacity of these enzymes to oxidize S moieties is universally accepted (Bernards et al, 1999;Quiroga et al, 2000;Ros Barceló and Pomar, 2001;Holm et al, 2003;Sasaki et al, 2004), and this observation would explain why antisense suppression of basic peroxidases in transgenic plants produces decreased levels of both G and S lignins (Blee et al, 2003), while antisense suppression of acidic peroxidases produces only decreased levels of G lignins (Li et al, 2003).…”
Section: Discussion Basic Zeprxs In Sccmentioning
confidence: 99%
“…Both peroxidases and laccases have been shown to be active in woodforming tissues of Populus and to be capable of polymerizing both monomethoxylated (guaiacyl G) and bimethoxylated (syringyl S) monolignols into lignin-like polymers in vitro (Christensen et al, 1998;Ranocha et al, 1999;Sasaki et al, 2004Sasaki et al, , 2008. More recently, laccases LAC4/IRX12, LAC11, and LAC17 (Zhao et al, 2013) were demonstrated to act redundantly during vessel element and fiber lignification.…”
Section: Spatially Separated Expression Of Phenoloxidases May Enable mentioning
confidence: 99%
“…Nevertheless, horseradish peroxidases (HRP) appear to be incapable of oxidizing the lignin polymer [5] although most DHP studies have employed HRP to oxidize coniferyl alcohol. The HRP displays poor oxidative capacity towards sinapyl alcohol [187]. Sasaki et al [187] have described a cell wall-bound peroxidase that oxidized sinapyl alcohol and polymeric lignin.…”
Section: Delignifying Enzymesmentioning
confidence: 99%
“…The HRP displays poor oxidative capacity towards sinapyl alcohol [187]. Sasaki et al [187] have described a cell wall-bound peroxidase that oxidized sinapyl alcohol and polymeric lignin.…”
Section: Delignifying Enzymesmentioning
confidence: 99%